PERFORMANCE ASSESSMENT OF AN ELECTRICITY MICROGENERATION PLANT USING BIOGAS - Cristela M. Siebert; Samuel N. M. de Souza; Doglas Bassegio; Deonir Secco; Waldir M. Machado Junior (Engenharia Agrícola)
ABSTRACT The operating costs and investment in microgeneration plants are high, and the maximum efficiency of the process should be targeted such that farmers can obtain the best financial returns. In this study, the efficiency of a microbiogas plant was estimated using a methodological analysis that involved a biodigester mass balance and plant energy balance. The plant had two biodigesters and an engine generator. The biodigesters under study were considered low tech. The results showed 65% utilization of the volatile solids present in the substrate by the biodigesters, producing biogas with an average methane concentration of 57%. The equipment necessary for the operation of the system consumed 19.45% of the energy produced, and most of this energy was used for the transportation of substrates. The energy balance of the plant indicated an energy efficiency of 27.24% during the production process. The hydraulic retention time, pH, intermediate/partial alkalinity ratio, and organic loading rate indicate that reactor A is underutilized, has a low nutrient supply, and may result in low methane production. These indicators suggest that biogas production and quality can be improved by better distribution of substrates among the digesters.